2016
DOI: 10.1177/0894486516656276
|View full text |Cite
|
Sign up to set email alerts
|

Incumbents’ Attitude Toward Intrafamily Succession

Abstract: Incumbents’ attitude toward intrafamily succession (IFS) is a critical individual-level determinant of family firms’ IFS intention, which is, in turn, an important component of family business essence. Knowledge about its antecedents, however, is fragmented and very limited. Drawing on the theory of planned behavior and general attitude literature, hypotheses about the situational and individual antecedents of family firm incumbents’ attitude toward IFS were developed and tested with a sample of 274 Italian fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 120 publications
1
92
0
2
Order By: Relevance
“…Finally, there may be other factors that affect innovativeness in family SMEs, including imminence of succession (Chua, Chrisman, and Sharma, 2003) and family firm incumbents' attitude toward intrafamily succession (De Massis, Sieger, Chua, and Vismara, 2016). These factors suggest additional ways in which family functionality and family owners' noneconomic goals affect family firms' capacity to innovate.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Finally, there may be other factors that affect innovativeness in family SMEs, including imminence of succession (Chua, Chrisman, and Sharma, 2003) and family firm incumbents' attitude toward intrafamily succession (De Massis, Sieger, Chua, and Vismara, 2016). These factors suggest additional ways in which family functionality and family owners' noneconomic goals affect family firms' capacity to innovate.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Aside from the future research directions suggested in the discussion of findings and limitations, there may be other factors that affect internationalization in publicly traded family firms. The imminence of succession (Chua, Chrisman, & Sharma, 2003) and the family firm incumbents' attitudes toward intra-family succession (De Massis, Sieger, Chua, & Vismara, 2016) are two. The effects of generational differences on internationalization might also vary in family firms depending upon other variables such as their entrepreneurial orientation (Dess & Lumpkin, 2005;Dess, Lumpkin, & McGee, 1999;Lumpkin, Wales, & Ensley, 2007).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…This gap reflects the skew of family business literature toward incumbents rather than next-generation members (De Massis, Sieger, Chua, & Vismara, 2016), and the emphasis of succession literature on firm level processes and outcomes rather than on individual or family level predictors (Daspit, Holt, Chrisman, & Long, 2016;Jaskiewicz & Dyer, 2017).…”
Section: Introductionmentioning
confidence: 99%